2005
DOI: 10.11150/kansenshogakuzasshi1970.79.656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of Sixteen Cases with Pulmonary Cryptococcosis Mainly with

Abstract: Clinical studies of sixteen cases with pulmonary cryptococcosis, during the past six years between 1998 and 2004, were peformed mainly with respect to serum cryptococcal antigen titer. Serum cryptococcal antigen was positive in twelve of 16 cases, the other three cases were diagnosed by VATS, the other one by positive culture of cryptococcus in BALF. In these twelve cases, the serum cryptococcal antigen titer was continuously tested after treatment. The serum cryptococcal antigen titer decreased from half to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…On day 2 of admission, his clinical course was complicated by the worsening of his tachypnea and hypoxemia, which required endotracheal intubation and mechanical ventilation. A transthoracic echocardiogram revealed a left ventricular ejection fraction of 15% (55-65), without segmental wall motion abnormalities, and a systolic pulmonary artery pressure of 49 mmHg (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These results were unchanged from a previous echocardiogram, which was obtained a few months prior to admission.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…On day 2 of admission, his clinical course was complicated by the worsening of his tachypnea and hypoxemia, which required endotracheal intubation and mechanical ventilation. A transthoracic echocardiogram revealed a left ventricular ejection fraction of 15% (55-65), without segmental wall motion abnormalities, and a systolic pulmonary artery pressure of 49 mmHg (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These results were unchanged from a previous echocardiogram, which was obtained a few months prior to admission.…”
Section: Introductionmentioning
confidence: 82%
“…Cryptococcal pneumoniainduced respiratory failure and ARDS are associated with a high rate of mortality (4,22). Blood cultures are positive in >50% of patients with disseminated cryptococcal disease (4, 23,25). Serum samples are usually positive for cryptococcal antigen, with markedly elevated titers in patients with cryptococcal pneumonia (4, [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, helpful diagnostic tools such as QuantiFERON test and serum cryptococcal antigen test should be considered. However, Dotsu et al reported that sensitivity of the serum cryptococcal antigen test was decreased when the nodule size measured <15 mm [ 16 ]. Although we did not examine serum cryptococcal antigen on admission, its result would likely have been negative due to the small nodule size in this case.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that cryptococcal PLB was undetectable in the serum of cryptococcosis patients with active or persistent infection who, with the exception of two human cases of localized lung infection, had high capsular polysaccharide antigen titers in serum. The absence of capsular antigen in the serum of patients with localized pulmonary cryptococcosis is unusual, but can occur in up to 25% cases (Dohtsu et al , 2005). The ELISA was rapid and reproducible, was able to detect 3.9 ng mL −1 of PLB, and provided us with a simple and sensitive alternative means of quantifying PLB in culture supernatants of both C. neoformans var.…”
Section: Discussionmentioning
confidence: 99%